The impact of phosphorus on the immune system and the intestinal microbiota with special focus on the pig. Issue 1 (25th May 2015) - Heyer, Charlotte M.E.; Weiss, Eva; Schmucker, Sonja; Rodehutscord, Markus; Hoelzle, Ludwig E.; Mosenthin, Rainer; Stefanski, Volker
Abstract : There is increasing interest in dietary ingredients that are appropriate to support digestive and immune functions, but also maintain a stable microbial ecosystem in the gastrointestinal tract (GIT), particularly in weaned pigs. P is an essential nutrient for both microbes and their host, as it is involved, for example, in bone formation, energy metabolism, cellular signalling and stabilisation of cell membranes. Non-ruminant animals have limited access to phytate, the main storage form of P in plant seeds. The release of P bound to phytate requires phytase activity of plant or microbial origin, resulting in the formation of variable phosphorylated inositol phosphates (InsPs). The present review focuses on interactions between variations in dietary P supply, the immune system of the host, and the intestinal microbial ecosystem. Although results on the interaction between P and the immune system are inconsistent, several studies in different species have shown a positive impact of dietary P and phytase addition on the adaptive immune response. Recent studies with pigs suggest that P supply may influence intestinal microbial composition and activity. Individual InsPs or phosphate may also affect properties of pathogenic micro-organisms, such as metabolism or virulence. In conclusion, P may be considered as part of an integrated approach to support immune functions and maintain a stable microbial ecosystem in the GIT, thereby providing a barrier against potential pathogens. Within this regard, differences in phytate-P content and intrinsic phytase activity of plant feedstuffs, as well as the formation of individual InsPs, have to be taken into account.